Single jejunal blowout perforation following blunt abdominal trauma: Diagnostic dilemma - Sunder Goyal; Snigdha Goyal; M K Garg (Wolters Kluwer Medknow Publications, 2013)
Single isolated jejunal perforation (IJP) due to blunt abdominal trauma is uncommon and most often occurs with road traffic accidents. The diagnosis of traumatic single IJP is challenging as there are minimal clinical features initially. For most favorable results, strict monitoring, a high index of clinical suspicion, and the help of available appropriate diagnostic tools like diagnostic peritoneal lav age (DPL)/focused abdominal sonography for trauma (FAST) are preferable. Here we report a case of IJP following blunt trauma abdomen.